Dynamics of Inflammatory Response in Autoinflammatory Disorders: Autonomous and Hyperinflammatory States - Gül, Ahmet (Frontiers in Immunology, 2018)
Autoinflammatory diseases were originally defined as a group of monogenic disorders associated with seemingly unprovoked inflammatory episodes mediated mainly by the innate immune system and without direct involvement of adaptive immunity. The renewed concept encompasses a larger group of disorders including multifactorial diseases, which share the same inflammatory and clinical features with the monogenic disorders. Coining of the “auto” prefix to these inflammatory diseases suggests a constitutively active and self-augmenting innate immune response, but only a subgroup of them including cryopyrin-associated periodic syndrome (CAPS), associated with dominantly inherited gain-of-function NLRP3 variants, fits well with the definition of the “autonomous” inflammatory conditions. However, the “autoinflammation” concept also includes another group of disorders characterized by episodes of exaggerated inflammatory response only when challenged by certain triggers. The dynamics of this latter group can be better defined as a “hyperinflammatory” state, which shares similar characteristics with the innate memory or trained immunity. Differentiation of “autonomous” and “hyperinflammatory” states of autoinflammatory disorders can provide additional insights to understand their pathogenesis and develop better management strategies since both conditions may have different inflammatory dynamics affecting the severity and frequency of clinical findings and treatment responses.